Why Is Workplace Sexual Harassment Underreported? The Value of Outside Options Amid the Threat of Retaliation - Gordon B. Dahl; Matthew Knepper (Center for Economic Studies and ifo Institute (CESifo), 2021)
Why is workplace sexual harassment chronically underreported? We hypothesize that employers coerce victims into silence through the threat of a retaliatory firing, and test this theory by estimating whether external shocks that reduce the value of a worker's outside options exacerbate underreporting. Under mild assumptions, a rise in the severity of formal complaints is indicative of increased underreporting. Combining this insight with an objective measure of the quality of charges filed with the Equal Employment Opportunity Commission (EEOC), we perform two analyses. First, we assess whether workers report sexual harassment more selectively during recessions, when outside labor market options are limited. We estimate the fraction of sexual harassment charges deemed to have merit by the EEOC increases by 0.5-0.7% for each one percentage point increase in a state-industry's monthly unemployment rate. The effect is amplified in industries employing a larger fraction of men and in establishments with a higher share of male managers. Second, we test whether less generous UI benefits create economic incentives for victims of workplace sexual harassment to remain silent. We find the selectivity of sexual harassment charges increases by more than 30% in response to a 50% cut to North Carolina's Unemployment Insurance (UI) program following the Great Recession.
Keywords: J71; J78; 330; sexual harassment; unemployment; unemployment insurance